The genus Zelentia is an amphi-boreal taxon expanded to include three new species from the North Pacific and Atlantic oceans (Gastropoda: Nudibranchia: Trinchesiidae) - Korshunova, Tatiana; Fletcher, Karin; Lundin, Kennet; Picton, Bernard; Martynov, Alexander (Zootaxa, 2018)
The taxonomy of Zelentia Korshunova, Martynov & Picton, 2017, a genus of aeolidacean nudibranchs recently separated from Trinchesia Ihering, 1879, is reviewed. Using previous and novel data, including the defining morphological characters of a supplementary gland inserted into the penis, which is also armed with stylet, it is demonstrated that the genus Zelentia is a well-established amphi-boreal taxon. A phylogenetic tree and haplotype network for species of the genus Zelentia are provided. A new species from the Northeastern Pacific, Zelentia willowsi sp. nov. and a second Northeastern Pacific species, Zelentia nepunicea sp. nov., previously thought to be “Cuthona” pustulata (Alder & Hancock, 1854), are described using morphological and molecular data. A new species from the North Atlantic and sub-Arctic White Sea, Zelentia roginskae sp. nov., is also described using morphological and molecular data. The Northeastern Pacific Zelentia nepunicea sp. nov. and“Cuthona” punicea Millen, 1986, which externally share a similar reddish colouration, are shown to belong to two different families since “Cuthona” punicea possesses a supplementary gland inserted into the vas deferens and an unarmed penis, characters of the genus Cuthonella Bergh, 1884, belonging to the Cuthonellidae family. Despite belonging to different families and having significant internal differences, externally Cuthonella punicea and Zelentia nepunicea sp. nov. appear similar, thus the new sympatric species of Zelentia is given the name Z. nepunicea sp. nov. which means non punicea. To facilitate identification and avoid further confusion we provide a comparative table which encompasses diagnostic morphological data for Northeastern Pacific species of the families Cuthonidae, Cuthonellidae and Trinchesiidae which are externally similar to the described new taxa.